The effect of weather types on the frequency of childhood asthma admissions in Athens, Greece - Nastos, P. T.; Paliatsos, A. G.; Priftis, K. N.; Kaldellis, J. K.; Panagiotopoulou-Gartagani, P.; Tapratzi-Potamianou, P.; Zachariadi-Xypolita, A.; Kotsonis, K.; Kassiou, K.; Saxoni-Papageorgiou, P. (Fresenius Environmental Bulletin, 2006)
The aim of this study was to investigate the influence of weather conditions on the number of admissions for childhood asthma in Athens, Greece. Daily counts of childhood asthma admissions (2764) of the three main Children's Hospitals in Athens, from hospital registries during a 3-year period (2001-2003), were obtained. The meteorological data reviewed consists of daily values of 20 parameters recorded at the National Observatory of Athens during the study period: maximum temperature (Tmax); minimum temperature (Tmin); mean temperature (Tmean); diurnal temperature range (Trange = Tmax - Tmin); day-to-day change in maximum temperature (Ξ”Tmax); day-to-day change in minimum temperature (Ξ”Tmin); day-to-day change in mean temperature (Ξ”Tmean); day-to-day change in diurnal temperature range (Ξ”Trange); mean relative humidity (RH); day-to-day change in mean relative humidity (Ξ”RH); mean water vapor pressure (e); day-to-day change in mean water vapor pressure (Ξ”e); mean atmospheric pressure at sea level (P); day-to-day change in mean atmospheric pressure (Ξ”P); mean irradiance (I); day-to-day change in mean irradiance (Ξ”I); mean sunshine (S); day-to-day change in mean sunshine (Ξ”S); mean wind speed (v) and day-to-day change in mean wind speed (Ξ”v). The performed statistical methods were: (i) Pearson's Ο‡2 test, using contingency tables and (ii) Factor and Cluster analysis. The application of this 2-part analysis revealed the relationship between the extracted weather types and the frequency of childhood asthma admissions in Athens. The results showed that weather conditions with low temperature, low water vapor pressure and cold anticyclonic presence were significantly correlated with an increase in the number of asthma admissions among children in Athens. The impact of these specific weather conditions on asthma exacerbation should be interpreted either by the asthmogenic effect of humid weather per se or the association with respiratory viral infection, mold's and mites' allergy. Β© by PSP 2006.
Keywords: Acari; asthma; Athens; Athens [Attica]; Attica; child health; Childhood asthma; Eurasia; Europe; Greece; Southern Europe; Weather; Weather types